Elucidating the role of Cdk13 and Prkd1 in heart development and congenital heart disease - Waheed Ullah, Qazi (2024)
Congenital heart disease (CHD) is the most common congenital anomaly, with an overall incidence of approximately 1% in the United Kingdom. Genetic causes include chromosomal abnormalities, copy number variants, and point mutations. Recent studies have used whole exome sequencing (WES) in large CHD cohorts to better under-stand the genetic aetiology of CHD. This includes a study of 1891 pro-bands by our group in collaboration with others, which identified three novel genes – Cyclin Dependant Kinase - 13 (CDK13), Protein Kinase D1 (PRKD1) and Chromodomain Helicase DNA Binding Protein 4 (CHD4), in patients with syndromic CHD. For this PhD research, two of them, CDK13 and PRKD1, were selected to characterize their role in heart development and CHD. CDK13 encodes a cyclin-dependent kinase phosphorylating the carboxyl-terminal domain (CTD) of RNA polymerase II (RNAPII) and is involved in RNA processing and splicing though its true associating partners are still unknown. PRKD1 (also known as PKCµ) encodes a serine/threonine protein kinase, which is involved in a variety of fundamental cellular functions including the regulation of “rat sarcoma” (RAS) signalling, cell survival, migration, differentiation, proliferation and adhesion, and Golgi transport. Taken together, these studies demonstrate a likely critical, though uncharacterized, role for CDK13 and PRKD1 in the embryonic heart. To obtain a greater appreciation for the role that these essential protein kinases play in cardiogenesis and CHD, one Cdk13 (Cdk13tm1b) and two Prkd1 (Prkd1em1 & Prkd1em2) transgenic mouse models were analysed. The Cdk13tm1b and Prkd1em1 carried loss of function (LOF) mutations whereas Prkd1em2 carried the most common missense (referred to as humanised) mutation. High resolution episcopic microscopy (HREM) affords detailed morphological 3D analysis of the developing heart and provides evidence for the role of Cdk13 and Prkd1 in normal car-diac development and CHD. The results from this research show that homozygous mutation of Cdk13 and Prkd1 are associated with severe forms of CHD and are embryonically lethal. However, survival to at least postnatal day 7 is possible in case of Prkd1-LOF (noticed once). Moreover, six mice harbouring homozygous missense mutation (G598R) of Prkd1 also survived to adult stage. No live-birth with homo-zygous Cdk13-LOF mutation was seen. Even in heterozygotes with LOF, cardiac differences occur, albeit at low penetrance, suggesting that one wild type allele of Cdk13 and Prkd1 are sufficient to support normal heart development in ~82 cases with Cdk13-LOF % (n = 39/47) and Prkd1-missense mutation (n = 53/64), and 98% cases with Prkd1-LOF mutation (n = 54/55). Heterozygotes with Prkd1-missense muta-tion are more deleterious in terms of CHD penetrance (coupled with reduced protein expression) than those with Prkd1-LOF mutation. RNA-Seq. analysis in Cdk13-LOF mouse comparing WT with homozygous hearts showed significant enrichment of gene ontology (GO) terms related to cardiovascular system (CVS) development and significant suppression of the morphogenetic pathways, processes related to RNA processing as well as CDK13 role as a kinase at RNA polymerase-II in the mutant hearts. Overall, this research demonstrates a vital role of Cdk13 and Prkd1 in heart development and the aetiology of CHD.